A Bibliometric Analysis of the Development of Organic Agriculture Research in the World - Loso Judijanto; Haryono Haryono (West Science Agro, 2024)
This study presents a comprehensive bibliometric analysis of global research on organic agriculture, examining publication trends, thematic focuses, author collaborations, and international research networks. By analyzing data from major academic databases, this study identifies the core themes that define organic agriculture research, including sustainable agriculture, soil fertility, and crop rotation, and highlights emerging topics such as innovation, agroecology, and economic viability. The analysis also reveals strong international collaboration, with significant contributions from North America, Europe, and Asia, and identifies opportunities for expanding partnerships in underrepresented regions. These findings provide valuable insights into the development and future directions of organic agriculture research, underscoring its relevance in addressing global sustainability challenges. The study serves as a useful resource for policymakers, researchers, and practitioners aiming to promote and expand organic agriculture as a sustainable alternative to conventional farming.